2013
DOI: 10.1103/physrevb.87.014305
|View full text |Cite
|
Sign up to set email alerts
|

Nonperturbative stochastic method for driven spin-boson model

Abstract: We introduce and apply a numerically exact method for investigating the real-time dissipative dynamics of quantum impurities embedded in a macroscopic environment beyond the weak-coupling limit. We focus on the spin-boson Hamiltonian that describes a two-level system interacting with a bosonic bath of harmonic oscillators. This model is archetypal for investigating dissipation in quantum systems and tunable experimental realizations exist in mesoscopic and cold-atom systems. It finds abundant applications in p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(131 citation statements)
references
References 158 publications
(257 reference statements)
3
128
0
Order By: Relevance
“…This pushes numerical methods even further toward their limits, [12][13][14][15][16][17][18][19][20] and many studies have hitherto focused on simpler analytical approaches 2,3 (master equations, for instance) that may fail at large dissipation and low temperatures.…”
Section: -11mentioning
confidence: 99%
“…This pushes numerical methods even further toward their limits, [12][13][14][15][16][17][18][19][20] and many studies have hitherto focused on simpler analytical approaches 2,3 (master equations, for instance) that may fail at large dissipation and low temperatures.…”
Section: -11mentioning
confidence: 99%
“…For example in [2], by solving an equivalent stochastic Schrödinger equation, the authors observed an exponential decay in the long time behaviour of the spin correlation functions.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…[1]). An example for the first situation can be found in [2] where the spin-boson Hamiltonian is used to investigate the real-time dissipative dynamics of quantum impurities embedded in a macroscopic environment. Relying on functional methods for quantum dissipative systems [3], the authors reformulated the original problem in terms of a stochastic Schrödinger equation with a Gaussian noise coupled linearly to the quantum system.…”
Section: Introductionmentioning
confidence: 99%
“…The qubit then evolves at later times according to the full spin-boson Hamiltonian (3), and progressively relaxes to its many-body ground state while energy is dissipated into the bath. This theoretical problem has been considered by a great variety of methods, such as quantum Monte Carlo [40,41], stochastic expansions [42][43][44], timedependent NRG [45,46], systematic variational dynamics [47], and analytical weak-coupling calculations [48][49][50][51], but mostly from the perspective of the qubit dynamics. Indeed, in addition to the relaxation properties of the qubit itself, we will examine here in depth the behavior of the states in the bath.…”
Section: Population Decay and Coherence Buildup A Sudden Quantumentioning
confidence: 99%